2001
DOI: 10.1111/j.1751-3928.2001.tb00078.x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration Patterns Related to Hydrothermal Gold Mineralizaition in Meta‐andesites at Dungash Area, Eastern Desert, Egypt

Abstract: : The hydrothermal alteration patterns associating with the gold prospect hosted by metavolcanics in the Dungash area, Eastern Desert of Egypt, were investigated in order to assign their relationship to mineralization. The metavolcanics of andesitic composition are generated by regional metamorphism of greenschist facies superimposed by hydrothermal activity. Epidote and chlorite are metamorphic minerals, whereas sericite, carbonates, and chlorite are hydrothermal alteration minerals. The auriferous quartz ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 15 publications
(9 reference statements)
2
10
0
Order By: Relevance
“…Furthermore, Almond et al (1984) and Hassaan and El Mezayen (1995) suggested the derivation of the ore fluids by metamorphism during ophiolite and/or island arc tectonic stages. This is consistent with Boyle (1979) who proposed a greenschist metamorphogenic model for the origin of gold (Helba et al 2001). Botros (2004) envisaged a combined metamorphic-magmatic origin for these fluids.…”
Section: Introductionsupporting
confidence: 86%
“…Furthermore, Almond et al (1984) and Hassaan and El Mezayen (1995) suggested the derivation of the ore fluids by metamorphism during ophiolite and/or island arc tectonic stages. This is consistent with Boyle (1979) who proposed a greenschist metamorphogenic model for the origin of gold (Helba et al 2001). Botros (2004) envisaged a combined metamorphic-magmatic origin for these fluids.…”
Section: Introductionsupporting
confidence: 86%
“…The veins depict alteration processes such as silicification, sulphidation, haematitization, carbonatization, sericitization, and K‐feldspar alteration (Figures ) that vary from the core zone to the selvages. According to Helba, Khalil, and Abdou (), gold and sulphide mineralization is particularly abundant in carbonate–sericite‐rich zones for intrusion‐related gold deposits. Both ore and gangue minerals define the margins of the veins.…”
Section: Discussionmentioning
confidence: 99%
“…Using ternary discrimination plots (Au–Ag–Cu and Au–Ag–Hg), the composition of the gold grains from Bétaré Oya was investigated (Figure ). Compositional fields (Chapman & Mortensen, ; Helba et al, ; Townley et al, ) were included in order to constrain the gold formation process and mineral system. A match to magmatic–hydrothermal vein‐type gold is suggested here for the Bétaré Oya gold grains (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Signifi cant changes in SiO 2 in the samples can be attributed to silica inundation or silica leaching. Gains in Fe 2 O 3 + MgO accompanied by loss in CaO + Na 2 O are being attributed to the breakdown of plagioclase ( Helba et al , 2001;Querubin & Yumul, 2005 ). In contrast, the increase in CaO + Na 2 O suggests the possible occurrence of calcite.…”
Section: Discussionmentioning
confidence: 99%